BEBERAPA FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN SEKTORINDUSTRI FOOD AND BEVERAGE DIBURSA EFEK INDONESIA PERIODE 2015-2019 - Haloho, Rexy; Munthe, Kornel; Purba, Saut (LPPM Universitas Katolik Santo Thomas Medan, 2022)
This study aims to analyze the effect of asset structure, profitability, sales growth, and liquidity on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange. The population in this study were 26 food and beverage companies. By using purposive sampling method in sampling, 11 companies were obtained as samples, with a study period of 5 years. The data analysis technique used is multiple linear regression analysis and hypothesis testing using t test and F test with of 5%. The results showed that: (a) asset structure had a positive and significant effect on capital structure, profitability and sales growth had a negative and insignificant effect on capital structure, and liquidity had a negative and insignificant effect on capital structure in food and beverage companies listed on the Stock Exchange. Indonesian Securities, (b) asset structure, profitability, sales growth, capital structure, and liquidity simultaneously have a significant effect on the capital structure of food and beverage companies listed on the Indonesia Stock Exchange.